A Study on The Factors Impacting Retirement Planning Among Low-Income Workers in The Northern Region, Malaysia (Journal of Entrepreneurship and Business, 2022)
Since the world's ageing population is expanding quickly, retirement planning has been identified as one of the top concerns of all nations. As a developing country, Malaysia has also been touched by this issue. Particularly, retirement planning among low income earners is frequently contested because of a lack of available financial resources among them. Therefore, this study aims to investigates the factors influencing the retirement planning among low income workers at the Northern Region, Malaysia. This study anticipated that saving attitude, financial socialisation, financial literacy, and demographic characteristics could all have an impact on retirement planning. A quantitative method with convenience sampling was applied in this study. This study used an online questionnaire to collect primary data from working adults with limited financial resources. Using SPSS, the data that was gathered was examined. Multiple linear regression and Pearson Correlation Analysis were both used in the analysis. The findings demonstrate that ethnicity and state, as well as financial socialisation, saving attitudes, and financial literacy, have a substantial impact on retirement planning among low-income employees in Malaysia's Northern Region. This study will give researchers, policymakers, governments, and Employee Provident Fund a detailed picture of retirement planning among low-income workers in Malaysia's Northern Region (EPF).
Keywords: Array; Array; Array; Array; Array